Increased Incidence of Hypertrophic Pyloric Stenosis in Esophageal Atresia Patients - van Beelen, Nicole Wilhelmina Gerarda; Mous, Daphne S.; Brosens, Erwin; Klein, Annelies de; Ven, Cornelis P. van de; Vlot, John; IJsselstijn, Hanneke; Wijnen, Rene (European Journal of Pediatric Surgery, 2014)
Introduction Around half of patients with esophageal atresia (EA) have additional congenital anomalies. Hypertrophic pyloric stenosis (HPS) in these patients is less known, with only 36 cases reported in the past literature. This retrospective study aimed to establish the incidence and clinical presentation of EA patients in combination with HPS in our hospital.Materials and Methods A retrospective study was based on the medical histories from all patients with EA who underwent surgical repair in our hospital from 1988 through 2012.Results Of 267 patients with EA, 20 also developed HPS (7.5%). The latter group showed male predominance, 90 versus 60% in the EA without HPS group. The first symptoms of HPS were mostly vomiting and/or feeding intolerance (n = 19). The diagnosis was mostly delayed, with a median of 6 days (range, 1–21 days).Conclusions This is the first report on the high incidence of HPS in a large series of EA patients. The incidence found is 30 times higher than that in the normal population. HPS should be considered when patients show recurrent or persisting vomiting and feeding intolerance after surgery. The reason for the higher incidence should be further investigated.
Keywords: esophageal atresia; hypertrophic pyloric stenosis; risk factors; incidence; pyloromyotomy